A QUANTITATIVE ANALYSIS OF TRIGGER FACTORS INFLUENCING COMPANIES FAILURE IN ITALY - Francesca di Donato; Luciano Nieddu (European Scientific Journal, ESJ, 2014)
In this paper the problem of firms‘ failures will be considered. Theaim is to determine which are the trigger factors that can predict the inabilityof a firm to cover its obligations. The problem will be tackled both from across-sectional and a longitudinal point of view using non parametric andsemi-parametric statistical models that allow to gain information from thedata without making too many assumptions.